Silent Reading and Reading Aloud for Better Comprehension and Speaking Motivation: A Comparative Study - Subedi, Rabindra (Kanakai Journal, 2022)
This article compares the effectiveness of reading aloud and silent reading for comprehension and speaking motivation. The data were taken from the ninth graders of a community school of Jhapa, Nepal. The students were divided into two groups and each were asked to read ten sample comprehension questions. The groups were provisioned to have a silent reading and reading aloud differently. Each group was given just five minutes of time- two times a day- for three weeks and were measured for their scores. Conclusions were drawn comparing the pre- test and post- test results and by closely observing their oral participation in the class. The results showed that reading aloud is more effective than silent reading for comprehension and speaking encouragement.